Elevated ABCB1 Expression Confers Acquired Resistance to Aurora Kinase Inhibitor GSK-1070916 in Cancer Cells - Wu, Zhuo-Xun; Yang, Yuqi; Wang, Jing-Quan; Zhou, Wen-Min; Chen, Junyu; Fu, Yi-Ge; Patel, Ketankumar; Chen, Zhe-Sheng; Zhang, Jian-Ye (Frontiers in Pharmacology, 2021)
The emergence of multidrug resistance (MDR) has been a major issue for effective cancer chemotherapy as well as targeted therapy. One prominent factor that causes MDR is the overexpression of ABCB1 transporter. In the present study, we revealed that the Aurora kinase inhibitor GSK-1070916 is a substrate of ABCB1. GSK-1070916 is a newly developed inhibitor that is currently under clinical investigation. The cytotoxicity assay showed that overexpression of ABCB1 significantly hindered the anticancer effect of GSK-1070916 and the drug resistance can be abolished by the addition of an ABCB1 inhibitor. GSK-1070916 concentration-dependently stimulated ABCB1 ATPase activity. The HPLC drug accumulation assay suggested that the ABCB1-overexpressing cells had lower levels of intracellular GSK-1070916 compared with the parental cells. GSK-1070916 also showed high binding affinity to ABCB1 substrate-binding site in the computational docking analysis. In conclusion, our study provides strong evidence that ABCB1 can confer resistance to GSK-1070916, which should be taken into consideration in clinical setting.